PENDIDIKAN SOSIAL KEMASYARAKATAN DALAM HADITS: SEBUAH PENDEKATAN HISTORIS - Niimmasubhani Niimmasubhani (STAI Darul Quran Payakumbuh, 2016)
This article discusses a study of social life in hadiths using the historical approach. The purpose of the research is to make learners live in social cummunity well. They are expected to know, to understand, and to base their lives on al-Qur’an, as a result, al-Qur’an and hadiths really stick in their hearts. Today, Muslim learners tend to neglect educative messages and values from those resources, in spite of applying them in social lives. Actually Moslems must care for each other, for instance, neighbors to neighbors to omit starvation. Besides, Moslems are also recommended to build a good relationship with non-Moslem society, such as manner of action, cooperation, and belief based on Islamic regulation. Through education of social relationships, it is expected to be an instrument to build social awareness, behavior, and skill for children. In order to reach the purpose of the social education illustrated above, educative messages deriving from al-Qur’an and hadiths like prophet Muhammad’s words, character, and obligation, are absolutely needed.